2021
DOI: 10.1002/admi.202002231
|View full text |Cite
|
Sign up to set email alerts
|

CsPbBr3 QDs Modified Vertically Layered MoS2/Si Heterojunction for Fast UV–vis–NIR Spectrum Flexible Photodetectors

Abstract: The CsPbBr3 quantum dots (QDs) modified vertically layered MoS2/Si (V‐MoS2/Si) heterojunction is successfully prepared. It is found that the resulting photodetector realizes the UV–vis–NIR broad‐spectrum detection with good sensitivity and fast photoresponse speed. Typically, the responsivity and response/recovery time towards 808 nm reach up to 0.975 A W−1 and 6.8/6.7 ms, respectively. Furthermore, it is demonstrated that with the modification of CsPbBr3 QDs, the responsivities of the pure V‐MoS2/Si‐based pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…The topography information on the different OSC and perovskite films can be found in Figures S1 and S2 including atomic force microscopy (AFM) and SEM images, indicating that the surface of the prepared films is continuous and uniform, which meets the standards of photodetectors. The UV–vis absorption spectra of both the perovskite and OSC films are shown in Figure c, and the absorption peaks of CsPbCl 3 , CsPbBr 3 , C8-BTBT, and pentacene appear around 420, 535, 320, and 710 nm, respectively, which are consistent with previous findings, and the relevant optical band gaps could be extracted from this figure. …”
Section: Resultssupporting
confidence: 89%
“…The topography information on the different OSC and perovskite films can be found in Figures S1 and S2 including atomic force microscopy (AFM) and SEM images, indicating that the surface of the prepared films is continuous and uniform, which meets the standards of photodetectors. The UV–vis absorption spectra of both the perovskite and OSC films are shown in Figure c, and the absorption peaks of CsPbCl 3 , CsPbBr 3 , C8-BTBT, and pentacene appear around 420, 535, 320, and 710 nm, respectively, which are consistent with previous findings, and the relevant optical band gaps could be extracted from this figure. …”
Section: Resultssupporting
confidence: 89%
“…The R and D * for WSe 2 /PbS QDs increased by 10 4 [26]. The R for MoS 2 /CsPbBr 3 QDs is about 0.9-1.02 A W −1 and the [43]. It can be concluded that the photoelectronic performance of our sample has been greatly improved after the QDs were coated, especially the photoresponse of the device in the near infrared region.…”
Section: Resultsmentioning
confidence: 69%
“…All-inorganic perovskite outperforms organic-inorganic hybrid perovskite in terms of ambient stability which is beneficial for real applications 260,261 . For example, all-inorganic cesium lead halides represent an emerging class of materials with excellent properties required for PDs such as high carrier mobility, long carrier diffusion length, and excellent visible light absorption 190,262 . Besides, the optical properties of CsPbX 3 nanocrystals (NCs) depend on their size and composition 190,260 .…”
Section: Cspbbr 3 /Tmd Heterostructuresmentioning
confidence: 99%